Chapter iSafeIncentive: Transforming Construction Safety Culture through Blockchain Incentives - Kim, Dohyeong; Soltani, Mehrtash; Pedro, Akeem; Yang, Jaehun; Tran, Si; Lee, Doyeop; Park, Chansik (Firenze University Press, 2024)
A significant challenge has long persisted in the construction industry: the lack of a robust incentive system to encourage and motivate workers to prioritize safety. While safety culture has been recognized as crucial, traditional approaches to incentivizing safe behaviours often encounter roadblocks, such as heavy documentation processes, recognition delays, and resource allocation difficulties. This paper addresses this problem by introducing an innovative approach to incentivize and cultivate a safety culture in the construction industry. iSafeincentive integrates blockchain technology and computer vision to develop a novel solution revolutionizing safety monitoring and incentive distribution. Computer vision technology is employed for real-time analysis of safety conditions based on on-site images, ensuring the immediate identification of safe practices. Simultaneously, blockchain technology safeguards the incentive distribution process's integrity and transparency, addressing traditional methods' shortcomings. The findings suggest that iSafeincentive offers an efficient and secure method for rewarding safe activities among workers. Furthermore, the integrated platform offers a promising pathway to enhance job site safety practices, ultimately reducing accidents and incidents within the construction sector